Energizing Green Cities in Southeast Asia : Applying Sustainable Urban Energy and Emissions Planning - Ostojic, Dejan R.; Bose, Ranjan K.; Krambeck, Holly; Lim, Jeanette; Zhang, Yabei (Washington, DC: World Bank, 2013)
Fast-growing cities in the East Asia and Pacific (EAP) region will define the region's energy future and its greenhouse gas (GHG) footprint. Rapid urbanization and growing standards of living offer a major opportunity to EAP cities to become the global engines of green growth by choosing energy efficient solutions to suit their infrastructure needs and by avoiding locking in energy-intensive infrastructure. The underlying studies in three EAP pilot cities show a clear correlation between investments in energy efficient solutions in all major infrastructure sectors and economic growth by improving energy and GHG emissions efficiency, cities not only help the global environment, but they also support local economic development through productivity gains, reduced pollution, and more efficient use of resources. Thus, the Bank is well positioned to assist municipal governments in building institutions, creating policies, developing long-term green growth plans that will attract financial support and investments from both the private sector and the donor community, and linking efficiency and low carbon programs to international concessional financing and funding, as well as to the private sector investors who will play an important role in achieving green growth objectives. This paper is organized as follows: part one focuses on urban energy use and GHG emissions in EAP; part two presents sustainable urban energy and emissions planning in three pilot cities; and part three gives sustainable urban energy and emissions planning guidebook: a guide for cities in EAP.